Studio Acusticum i Piteå - en mångsidig konserthall - Öqvist, Rikard; Tunemalm, Lennart; Tunemalm, Björn (Luleå tekniska universitet, Drift, underhåll och akustik, 2008)
Godkänd; 2008; 20080929 (ricokv)